2015
DOI: 10.1097/cmr.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Low numbers of tryptase+ and chymase+ mast cells associated with reduced survival and advanced tumor stage in melanoma

Abstract: The role of mast cells in cutaneous melanoma remains unclear. Tryptase and chymase are serine proteinases and major proteins in mast cell secretory granules. Therefore, this study aimed to investigate the presence of tryptase and chymase mast cells in benign and malignant cutaneous melanocytic lesions and in lymph node metastases of melanomas. The presence of positively stained mast cells was correlated with clinicopathological characteristics in invasive melanomas. Paraffin-embedded sections of 28 benign (13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 47 publications
(58 reference statements)
4
70
0
1
Order By: Relevance
“…In this respect, these findings confirm the results of Siiskonen et al [1] highlighting that this serine protease may also be serologically the expression of a protective role. However, our results also seem to highlight that ST may play a role in the early stage of the tumorigenesis.…”
supporting
confidence: 94%
See 2 more Smart Citations
“…In this respect, these findings confirm the results of Siiskonen et al [1] highlighting that this serine protease may also be serologically the expression of a protective role. However, our results also seem to highlight that ST may play a role in the early stage of the tumorigenesis.…”
supporting
confidence: 94%
“…We have read with much interest the article of Siiskonen et al [1]. For this reason, we would like submit our observation on the role of serum tryptase (ST) levels in patients with melanoma (MM).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Examples of the latter include breast cancer [17, 18], non-small-cell lung carcinoma [19], diffuse large B-cell lymphoma [20] and ovarian cancer [21]. In melanoma, partly conflicting clinical findings have been published (reviewed in [10]), with some studies indicating a detrimental impact of mast cells [22-24] whereas others have reported a positive correlation between mast cell presence and good prognosis [25]. …”
Section: Introductionmentioning
confidence: 99%
“…A low density of mast cells in invasive melanomas correlates with a poor prognosis, but the mast cell count is not correlated with survival in superficial melanomas [197]. In prostate cancer, mast cells are initially protumorigenic, but become dispensable at later stages [198, 199].…”
Section: Mast Cells In the Immune Landscape Of Cancermentioning
confidence: 99%